I'll teach my dog a lot of words - Frith, Michael K.; Eastman, P. D. (Philip D.) (New York : Beginner Books, 1999)
A youngster plans all the things he will teach his puppy.
Cover title.
Board pages.
Adapted from "I'll teach my dog 100 words".
Keywords: Stories in rhyme